A market for trading software issues. Issue 1 (3rd October 2019) - Rao, Malvika; Link, Georg J P; Marti, Don; Leak, Andy; Bodo, Rich
Abstract: The security of software is becoming increasingly important. Open source software forms much of our digital infrastructure. It, however, contains vulnerabilities which have been exploited, attracted public attention, and caused large financial damages. This article proposes a solution to shortcomings in the current economic situation of open source software development. The main idea is to introduce price signals into the peer production of software. This is achieved through a trading market for futures contracts on the status of software issues. Users, who value secure software, gain the possibility to predict outcomes and incentivize work, strengthening collaboration and information sharing in open source software development. The design of such a trading market is discussed and a prototype introduced. The feasibility of the trading market design is corroborated in a proof-of-concept implementation and simulation. Preliminary results show that the implementation works and can be used for future experiments. Several directions for future research result from this article, which contributes to peer production, software development practices, and incentives design.